In Vitro Propagation of Gymnocalycium mihanovichii LB2178 Agua Dulce (Cactaceae) and Genetic Stability Assessment Using Simple Sequence Repeat (SSR) Markers - Rotduang, Phakarat; Thawaro, Supawadee; Khawniam, Tassanee (Trends in Sciences, 2025)
The Gymnocalycium mihanovichii LB2178 Agua Dulce is a popular variety of cactus, known for its slightly raised skin known as “stripes” or bone pattern. It is also in high commercial demand. Therefore, the objective of this study were to study the effect of plant growth regulators and various explants fragmentation on callus induction and plant regeneration of G. mihanovichii LB2178 Agua Dulce and assessment genetic stability by SSR markers. The 1 cm seedlings of G. mihanovichii LB2178 Agua Dulce explant and callus were used as plant material. After 3 months of culture, the results showed that the explant sectioned longitudinally were cultured on MS medium supplemented with 2 mg/L 2,4-D, which gave the highest survival rate, 100 %, the highest callus induction, 100 % and the highest callus fresh weight, 2.72 g. The explant sectioned transversally were cultured on MS medium supplemented with 1 mg/L 2,4-D gave the highest anthocyanin contents, 0.00149 mg/gFW. The anatomical features of the callus derived from the tissue properties of the callus generated from transversely sectioned plant tissue culture, the epidermis layer is clearly visible, and there are vascular bundles arranged around the stem. The callus fragments were cultured on MS medium supplemented with 0.5 mg/L NAA and 3.5 mg/L BA gave the highest survival rate, 100 %, shoot induction, 90 %, a number of shoots, 2.20 shoots/explant and the shoot length, 0.28 cm. Assessment of genetic fidelity was performed on the G. mihanovichii LB2178 Agua Dulce micro propagated plantlets using SSR analysis with 8 SSR primers. The range of the chosen primers was 100 - 1,500 bp. The 4 of the 8 examined primers exhibited no polymorphism, whereas primer 4 displayed 83.33 % polymorphism. HIGHLIGHTS Effect of different explant fragmentation and different concentrations of 2,4 Dichlorophenoxyacetic acid (2,4-D) on callus induction of mihanovichii LB2178 Agua Dulce. Quantification of anthocyanins from callus of mihanovichii LB2178 Agua Dulce. Genetic stability of the mihanovichii LB2178 Agua Dulce using SSR markers. GRAPHICAL ABSTRACT